Where is Serbia’s stabilitocracy heading to? A Break from the past but without a future - Laurent Tournois (Eximia, 2024)
Since 2012, the gradual establishment of a new type of political regime, stabilitocracy in the Balkan region and Serbia in particular has raised many questions. From Europeanization (failed attempts), active and instrumentalized memory activism, and progressivism, to the foreign policy shift compared to Yugoslavia and, broadly speaking, the contestability of the liberal peacebuilding processes at work in Serbia, this paper engages in a critical discussion about its constituents and emphasizes the limits of the current Serbian political pattern beyond dogmatism and partisan discourses, and by showing greater openness to non-Western ways of thinking.